Meta Analisis : Pengaruh Pembelajaran Berbasis Permainan terhadap Motivasi dan Hasil Belajar Matematika Siswa - Nabil Makarim; Maman Fathurrohman; Jaenudin Jaenudin (Journal on Education, 2023)
Based on an analysis of existing data, it can be concluded that game-based learning has a significant impact on the motivation and Mathematics learning outcomes with a value of 1.007. Game-based learning is most effective when applied at the higher education and high school levels. The most effective type of game is digital gaming. Factors contributing to the impact of game-based learning on motivation and Mathematics learning outcomes include the rapid development of gaming technology and the ease of accessing gaming technology.